2022
DOI: 10.1111/jeu.12896
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan phagotrophy from predators to parasites: An overview of the enigmatic cytostome‐cytopharynx complex of Trypanosoma cruzi

Abstract: Eating is fundamental and from this basic principle, living organisms have evolved innumerable strategies to capture energy and nutrients from their environment. As part of the world's aquatic ecosystems, the expansive family of heterotrophic protozoans uses self‐generated currents to funnel prokaryotic prey into an ancient, yet highly enigmatic, oral apparatus known as the cytostome‐cytopharynx complex prior to digestion. Despite its near ubiquitous presence in protozoans, little is known mechanistically abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 150 publications
1
7
0
Order By: Relevance
“…This technique also allowed us to examine the localization of MyoF and MyoC and we found both motors also localized on these root fibers beginning at the cytostome entrance. The targeting of MyoF to these microtubules validates prior observations by Alves et al who, by using immuno-EM of epitope tagged MyoF on membrane extracted T. cruzi cytoskeletons, demonstrated that MyoF associates with SPC rootlet microtubules ((28) and reviewed in (12)). Our subsequent direct deletion of both MyAP paralogs using CRISPR/Cas9, resulted in endocytic-null parasites that phenocopied our myosin double deletion mutants ( ΔFΔC ) and we were able to completely restore this endocytic defect via complementation.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This technique also allowed us to examine the localization of MyoF and MyoC and we found both motors also localized on these root fibers beginning at the cytostome entrance. The targeting of MyoF to these microtubules validates prior observations by Alves et al who, by using immuno-EM of epitope tagged MyoF on membrane extracted T. cruzi cytoskeletons, demonstrated that MyoF associates with SPC rootlet microtubules ((28) and reviewed in (12)). Our subsequent direct deletion of both MyAP paralogs using CRISPR/Cas9, resulted in endocytic-null parasites that phenocopied our myosin double deletion mutants ( ΔFΔC ) and we were able to completely restore this endocytic defect via complementation.…”
Section: Discussionsupporting
confidence: 86%
“…In the absence of a clear in vitro growth defect exhibited by our endocytic null mutants, we continue to be faced with the central question regarding the ultimate role of endocytosis in this parasite's life cycle. Although we have speculated extensively in our prior reports as to why the SPC was retained specifically in those trypanosomatids that are transmitted via the insect feces, we still lack definitive evidence showing when or where endocytosis is essential in the parasite life cycle (12,19). However, what we have been able to demonstrate here using TEM and MSbased lipidomics analyses, is that these mutants have a dramatically reduced capacity to take in and store extracellular material such as host-derived cholesterol in their reservosome structures.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although not common, intracellular endocytosis has been documented in intracellular parasites spanning the taxa Apicomplexa (Spielmann et al , 2020 and references therein), Cryptomycota (Torruella et al , 2018) and Euglenozoa (Etheridge, 2022). The reduced dataset of phagotrophy-related proteins from Rozella allomycis correctly describes Trypanosoma cruzii and Leishmania braziliensis as capable of intracellular phagotrophy (Chasen et al , 2020; Halliday et al , 2020); whilst fails to assign Plasmodium falciparum and Toxoplasma gondii to this category.…”
Section: Discussionmentioning
confidence: 99%